Quality of life after septorhinoplasty measured with the Functional Rhinoplasty Outcome Inventory 17 (FROI-17) - Bulut, Cem; Wallner, Frank; Plinkert, Peter K.; Prochnow, Sebastian; Kuhnt, Christoph Paul; Baumann, Ingo (Rhinology, 2015)
BACKGROUND: Quality of life measurements are gaining in importance. The present study was conducted with the aim to compare patient satisfaction after septorhinoplasty according to their preoperative nasal deformity. METHODS: The patients completed two disease-specific questionnaires before their surgery: the Functional Rhinoplasty Outcome Inventory (FROI-17), the Rhinoplasty Outcome Evaluation (ROE) and as a general instrument, the Short Form 36 Health Survey (SF-36). The second measurement was taken during an outpatient examination 12 months after their primary septorhinoplasty. Patients were grouped in nasal axis deviation (NAD), nasal hump deformity (NHD) and NAD plus NHD. Additionally the patients with preoperative NAD and NAD+NHD were combined as deviated nose and compared to the non-deviation group. RESULTS: One hundred and two patients (51 male and 51 female) underwent primary septorhinoplasty. The ROE- and the FROI-17 overall score including all three subgroups showed significant postoperative improvements. Regarding the SF-36, the postoperative score improved significantly only in two scales (role-functioning physical and mental health). Looking at the the different QoL questionnaires, there were significant postoperative differences in regards to deviated versus non-deviated nose in the FROI-17 overall- and FROI-17 subscores (nasal and general symptoms) and in three scales of the SF-36 (vitality, social functioning, role-functioning emotional), showing a greater postoperative satisfaction in the deviated-nose patient. CONCLUSION: Patients with and without nasal deviation showed improved QoL after their surgery, as measured with the ROE, the FROI-17 and the SF-36. The patients with a nasal deviation showed a significantly better outcome, as measured with the FROI-17, in comparison with the non-deviated group.
Gesehen am 14.01.2021
Accepted: September 21, 2014